(untitled) (Revista Logos Ciencia & Tecnología, 2019)
The use of different types of technology is increasingly common in a larger and more varied group of people. In that sense, the students of the Professional Technical Program in Police Service and professional police officers of the Simón Bolívar Police School are no exception. Therefore, it was decided to study, from the quantitative and qualitative approaches, the type of practices, from the point of view of information security, which both groups apply in the daily life of their activities. Thus, an instrument consisting of five variables was validated and applied to determine strengths and weaknesses in information security. As a result, it was found that on average the behaviors and knowledge about information security are medium level and, therefore, the risk of being associated with problems in this area is high, which implies a need to redesign continuous training programs and keep in the academic curriculum subjects that include units referring to good information security practices.